Designing a Simple Folder Structure for a Complex Domain - Clemmensen, Torkil (Human Technology, 2011)
In this paper I explore a case of designing a simple folder structure for a new e-learning software program for a university study program. The aim is to contribute to the theoretical base for human work interaction design (HWID) by identifying the type of relations connecting design artifacts with work analysis and interaction design processes. The action research method was used, with the author in a double role as university researcher and project manager of a developer group within the university. Analysis was conducted through grounded theory, inspired by the HWID framework. The findings support the use of a holistic framework with asymmetrical relations between work analysis and design artifacts, and between design artifacts and interaction design. The paper concludes with suggestions for modifying the general framework, and recommendations for a HWID approach to design artifacts.